Relationship of Education, Age, Gender, Marital Status and Long Stay at Nursing Homes with Depression Events in Elderly - Mumulati, Safitri Burhan; Niman, Susanti; Indriarini, Maria Yunita (Universitas Muhammadiyah Semarang, 2020)
The prevalence of depression in the elderly in the world with an average age of 60 years is estimated there are 500 million people. The prevalence of depression in Indonesia based on the Information Center for Non-Communicable Diseases, elderly who experience depression by 11.6%. The effects of depression are decreased concentration and suicidal ideation. The purpose of this study was to identify the relationship between education level, age, sex, marital status and length of stay in nursing homes with the incidence of depression in the elderly. Research using quantitative methods with cross-sectional design. 101 elderly research respondents obtained by purposive sampling. The instrument used was a questionnaire and geriatric depression scale (GDS-15). Analysis of the data with chi-square test, the results obtained there is a relationship between the last education with the incidence of depression (p-value 0.014) and there is no relationship between age and the incidence of depression (p-value 0.132), there is no relationship between sex with the incidence of depression (p-value 0.273), there was no relationship between marital status and depressive events (p-value 0.187), there was no association of length of stay with depressive events (p-value 0.192), there was no relationship between family visits and depressive events (p-value 0.879).